PENGARUH RELIGIUSITAS, KUALITAS PELAYANAN, KUALITAS PRODUK TERHADAP LOYALITAS NASABAH TABUNGAN PADA PT. BANK ACEH SYARIAH KANTOR CABANG PEMBANTU DARUSSALAM - nurma yoni (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2019)
The purpose of research is to know the influence of religiality, quality of service, quality of products to customer loyalty savings at PT. Bank Aceh Branch Helper Darussalam. Sample of this research as much as 100 customers using the formula Slovin with a sample technique is purposive sampling. The type of research used in this study is quantitative. The data used is the primary data obtained by using questionnaires. The results of this study showed that religiusity, quality of service, the product quality is the simultaneous effect on customer loyalty savings at PT. Bank Aceh Branch maid Darussalam. A partial factor of religiusity and quality of service, the culinary products to give positive and significant impact on customer loyalty at PT. Bank Aceh, but one of the variables (product culitas) has a level of Lower influence than the variable religiusisity and quality of service.